DNA Functional Nanomaterials for Controlled Delivery of Nucleic Acid-Based Drugs - Lv, Zhaoyue; Zhu, Yi; Li, Feng (Frontiers in Bioengineering and Biotechnology, 2021)
Nucleic acid-based drugs exhibited great potential in cancer therapeutics. However, the biological instability of nucleic acid-based drugs seriously hampered their clinical applications. Efficient in vivo delivery is the key to the clinical application of nucleic acid-based drugs. As a natural biological macromolecule, DNA has unique properties, such as excellent biocompatibility, molecular programmability, and precise assembly controllability. With the development of DNA nanotechnology, DNA nanomaterials have demonstrated significant advantages as delivery vectors of nucleic acid-based drugs by virtue of the inherent nucleic acid properties. In this study, the recent progress in the design of DNA-based nanomaterials for nucleic acid delivery is summarized. The DNA nanomaterials are categorized according to the components including pure DNA nanomaterials, DNA-inorganic hybrid nanomaterials, and DNA-organic hybrid nanomaterials. Representative applications of DNA nanomaterials in the controlled delivery of nucleic acid-based drugs are exemplified to show how DNA nanomaterials are rationally and exquisitely designed to address application issues in cancer therapy. At the end of this study, the challenges and future development of DNA nanomaterials are discussed.